2015
DOI: 10.3168/jds.2014-7959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced whole-milk feeding in calves on subsequent first-lactation performance

Abstract: The objective of this study was to determine the effect of enhanced whole-milk (WM) feeding systems in calves from birth to 8wk of age on subsequent first-lactation performance. The experiment was conducted as a completely randomized design consisting of 2 treatment groups. At birth, 152 Holstein heifer calves were randomly assigned to 1 of 2 treatments: (i) 4L of WM/d or (ii) 8L of WM/d. The calves were bucket fed 2 or 4L of WM twice daily at 0700 and 1600h. Each calf was housed individually in temperature-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
7
32
3
2
Order By: Relevance
“…Postweaning ADG and hip width change (2 to 4 mo) were greater for calves fed less than 0.7 kg/d in the current study, resulting in BW and hip widths that did not differ by 4 mo of age. Yunta et al (2015) Yunta et al (2015) or Korst et al (2017), BW responses postweaning were similar to those reported in the current study and by other groups that fed increasing levels of milk or MR (Bach et al, 2013;Hill et al, 2013Hill et al, , 2016aKiezebrink et al, 2015).…”
Section: Feed Intake and Growth Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…Postweaning ADG and hip width change (2 to 4 mo) were greater for calves fed less than 0.7 kg/d in the current study, resulting in BW and hip widths that did not differ by 4 mo of age. Yunta et al (2015) Yunta et al (2015) or Korst et al (2017), BW responses postweaning were similar to those reported in the current study and by other groups that fed increasing levels of milk or MR (Bach et al, 2013;Hill et al, 2013Hill et al, , 2016aKiezebrink et al, 2015).…”
Section: Feed Intake and Growth Performancesupporting
confidence: 90%
“…Terré et al (2006) did not measure starter digestibility; however, during the weaning transition (10 d before through 36 d after weaning) calves fed 4 L/d had significantly greater purine derivative excretion compared with calves fed up to 6 L/d, which was correlated with starter intake and suggests greater starter digestibility for calves fed less MR. Purine derivative excretion has been used as an indirect measure of microbial protein flow from the rumen in early-weaned calves and can indicate extent of rumen development (Funaba et al, 1997). Though Terré et al (2006 fed less DM from MR than the current study (MR composition was fairly similar to the current study), other reports have shown decreases in starter intake when calves were fed greater than 6 L/d of milk (Kiezebrink et al, 2015) or 0.7 kg/d of DM from milk replacer (Yunta et al, 2015). Reductions in DM digestion postweaning as a result of feeding more MR came from reduced digestibility of fiber and sugar; this is similar to other recent measurements in the literature (Chapman et al, 2016; al., 2016a,b).…”
Section: Apparent Digestibilitymentioning
confidence: 49%
See 1 more Smart Citation
“…A 2016 survey of producers in the United States showed over half of the farms were feeding calves between 4-6 L per day [7]. Recent studies have shown that increasing milk allotment can increase average daily gain (ADG) pre-weaning, result in larger skeletal measurements at weaning, and decrease vocalizations caused by milk deprivation [12,13]. Milk allotments and starter intakes per calf for this model were reflective of experimental data [14].…”
Section: Feedmentioning
confidence: 94%
“…A linear increase (P ≤ 0.05) of hip height measurements was observed at 120 d of age according to the increasing liquid feed TS concentrations; however, no effect was observed after 150 d of age (Figure 1b). Kiezebrink et al (2015)…”
Section: Intake Performance and Growth Measurementsmentioning
confidence: 99%